PENGARUH KONSEP DIRI MELALUI AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Ilham Jati Puspa; Pujiati Pujiati; Edy Purnomo (JEE (Jurnal Edukasi Ekobis), 2015)
This study aimed to determine the effect of self-concept through learning activities on learning outcomes of Integrated Social Science at eighth grade students of SMP Negeri 2 Tumijajar academic year 2014/2015. The method used in this research was descriptive approach verification of ex post facto and surveys. The population in this study amounted to 181 students and 125 students sampled using simple random sampling technique. Data were collected through questionnaires and observation. Based on the data analysis it obtained the following results: (1) There is a positive and significant influence on the concept of self-learning activities. (2) There is a significant and positive impact of learning activities on learning outcomes of Integrated Social Science. (3) There is a positive and significant influence of the self concept on learning outcomes of Integrated Social Science. (4) There is a positive and significant influence of self concept through learning activities to the learning outcomes of Integrated Social Science.Penelitian ini bertujuan untuk mengetahui pengaruh konsep diri melalui aktivitas belajar terhadap hasil belajar IPS Terpadu siswa kelas VIII SMP Negeri 2 Tumijajar Tahun Pelajaran 2014/2015. Metode yang digunakan dalam penelitian ini adalah deskriptif verifikatif dengan pendekatan ex post facto dan survey. Populasi dalam penelitian ini berjumlah 181 siswa dan sampel 125 siswa dengan menggunakan teknik simple random sampling. Data dikumpulkan melalui angket dan observasi. Berdasarkan analisis data diperoleh hasil sebagai berikut: (1) Ada pengaruh yang positif dan signifikan konsep diri terhadap aktivitas belajar. (2) Ada pengaruh yang positif dan signifikan aktivitas belajar terhadap hasil belajar IPS Terpadu. (3) Ada pengaruh yang positif dan signifikan konsep diri terhadap hasil belajar IPS Terpadu. (4) Ada pengaruh yang positif dan signifikan konsep diri melalui aktivitas belajar terhadap hasil belajar IPS Terpadu.Kata kunci : aktivitas, hasil, konsep diri